Proteomic profiling for potential biomarkers of osteosarcoma patients / Zulaika Roslan - Roslan, Zulaika (2016)
Osteosarcoma (OS) is a common malignant bone tumour mainly occurs in children and young adults between the ages of 10 to 30 years. Although the advance of technology and improvement in chemotherapy treatment for OS has significantly improved the survival rate in recent years, its poor prognosis and unknown etiology continues to remain the major challenge in managing the disease progression. Therefore, the objectives of this study are to establish the serum protein profile of OS patients, to investigate the differential protein expression in pre and postchemotherapy and to identify the potential protein biomarkers relevant in OS cell migration. Serum and bone tissues biopsies were collected from healthy volunteers, pre- and post-chemotherapy OS patients. In this study, OS serum protein profile was established using a 4-plex iTRAQ analysis. Approximately 217 proteins with 104,214 spectra were acquired which includes low abundance proteins involved in biological processes and other protein classes. In addition, VCAM-1 was significantly altered (p<0.05) and shown to be highly expressed in post-chemotherapy OS serum. VCAM- 1 and ICAM-3 expression was then verified using western blot and immunohistochemistry staining to observe their roles in OS cell migrations. To date, this is the first differential protein expression study to use OS patients' serum at different stages for the protein profiling. The comprehensive data on the differentially expressed protein was successfully generated and the comparative study has revealed a significant amount of protein expressed has been significantly altered. This data could provide a new insight on the fundamental OS biological processes and further use as a potential biomarker for better OS prognosis.